Low-potassium Fuel Production from Empty Fruit Bunches by Hydrothermal Treatment Processing and Water Leaching. (August 2015) - Novianti, Srikandi; Nurdiawati, Anissa; Zaini, Ilman Nuran; Prawisudha, Pandji; Sumida, Hiroaki; Yoshikawa, Kunio
Abstract: Oil palm empty fruit bunches (EFB) are currently poorly utilized residue from palm oil processing but considered to be a potential feedstock for power generation. This study focuses on the combination of the hydrothermal (HT) conversion and the water leaching to produce low-potassium biofuel in order to reduce the slagging and fouling potential of the EFB. Combination of HT process at 180 °C and the water leaching not only reduced the ash content of the biomass but also reduced the potassium and chlorine contents, indicating the effectiveness of this combination to produce clean fuel. The total of 92% reduction of potassium can be obtained, while ash content can be significantly reduced from 4.9% to 0.9% wt. The potassium balance for HT process at 180 °C followed by the water leaching is also presented in this study. By calculating the metal oxide ratio in the ash, several slagging/fouling indices can be determined. The slagging and fouling tendency of EFB is improved after HT followed by the leaching process, lowering the tendency of biomass to harm the furnace.